(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2023)
Activating humanitarian diplomacy is one of the most important political tools that the state uses in implementing its foreign policy and national strategy. It also seeks to provide a helping hand to the oppressed in the humanitarian phenomenon. This idea was put forward in a bolder and clearer way after many convincing data and reasons emerged that justify commitment to it and reliance. It must be used as a permanent method of work in order to achieve sound starting points in overcoming disasters and crises, then formulate it within a philosophical, intellectual and legal framework that accommodates the definition of the fundamental concepts of humanitarian diplomacy and deals with its elements, components, goals and mechanisms for achieving them in the field, and developing solutions and hypotheses to confront the challenges of their application.